O31-3 Evaluating the connexion between healthcare worker and patient safety using the care bond framework. (1st September 2016) - Okyere, Daniel; Quinn, Margaret; Kriebel, David; Cifuentes, Manuel; Markkanen, Pia; Galligan, Catherine; Sama, Susan; Gore, Rebecca
Abstract : Objectives: We developed a conceptual framework, called the Care Bond (CareBond), to describe the relationship between healthcare worker and patient safety during the delivery of care and how psychosocial, work organisational and other occupational safety and health (OSH) factors can impact this relationship. We applied the framework in a population of home care (HC) aides in order to: 1) determine whether the CareBond could be measured quantitatively and 2) test the hypothesis that OSH factors can influence the CareBond. Methods: We developed the CareBond framework based on our previous studies and a review of the scientific literature. We evaluated the CareBond using a questionnaire in a cross-sectional survey of HC aides. Questionnaire responses used to measure dimensions of the CareBond were analysed using Principal Components Analysis; impacts of OSH factors on the CareBond were evaluated using Poisson regression. Results: 1, 249 HC Aides completed the questionnaire and contributed information on 3, 484 patient care visits. Three major dimensions of the CareBond were identified: HC worker safety, patient safety and collaboration. OSH conditions that weakened the CareBond included lack of equipment for patient mobility, prevalence ratio (PR) = 0.94; 95% confidence interval (CI) = 0.90, 0.99; experiencing slip, trip and falling hazards during the patient care visit (PR = 0.68; CI = 0.57, 0.81); presence of uncontrolled pets (PR = 0.78; CI = 0.64, 0.94); catching a patient while falling (PR = 0.94; CI = 0.87, 1.02); caring for a patient on home dialysis (PR = 0.70; CI = 0.52, 0.95); requirement of mopping the floors during the patient care visit (PR = 0.94; CI = 0.89, 1.00); and exposure to faeces (PR = 0.90; CI = 0.84, 0.97). Conclusions: The CareBond is a promising framework for characterising and quantifying the connexion between HC worker and patient safety. Factors that weaken the CareBond can be targeted for preventive interventions to improve OSH and quality of care.